Peran Kepemimpinan Transformasional dalam Meningkatkan Kinerja Karyawan SDN Brani Wetan 1 Kecamatan Maron Kabupaten Probolinggo - Purwanti, Putri Meilani; Junaedi, Deddy (Al-DYAS, 2025)
This study examines the role of transformational leadership in enhancing employee performance at SDN Brani Wetan 1, a public elementary school in Probolinggo Regency. The research is grounded in the limited exploration of the impact of transformational leadership on staff motivation and institutional achievements at the elementary school level, despite growing interest in educational leadership models. A qualitative case study design was employed, involving 11 purposively selected participants, including the principal, teachers, and administrative staff. Data were collected through interviews, observation, and documentation, and analyzed thematically using Miles and Huberman’s interactive model. The findings reveal that the principal demonstrates key characteristics of transformational leadership—such as inspirational motivation, intellectual stimulation, and individualized consideration—which positively influence teacher motivation, collaboration, and performance. The study concludes that transformational leadership plays a significant role in fostering a conducive work environment and improving staff performance. Theoretically, the study contributes to the discourse on leadership in primary education, while practically, it recommends enhancing principals’ leadership capacities and supporting policies that encourage adaptive and participatory leadership styles.